Stress levels in teaching staff of Social Sciences and Education Departments of the Universidad de Costa Rica, Western Campus in the face of COVID-19 situation - Lizano Lizano, Livan (2021)
The job stress is a current phenomenon faced by the academic population. It has been caused by many socioeconomic, and psychosocial factors, organizational culture, and some work-related elements. In fact, there was a study with the objective of analyzing the levels of stress caused in the academic population of Social Sciences and Education of the Universidad de Costa Rica, in which they took advantage from virtual modality and teleworking since COVID-19 pandemic. As a result, 70 teachers were tested by a social-active questionnaire where they answered a few questions about socio-demographic reality and job conditions under Cohen’s Perceived Stress Scale. For example, the levels of job stress found are regular, average M=25.74 and the 84.4% of the people asked are between average levels and high levels. In conclusion, the results based in analysis of multiple sectors define the variables like gender, age, whether they live with adults and older people who requires attention and the adaption to the virtual modality are predictor variables in the prevalence of stress received.